Reorienting categories as a members’ phenomena - Fitzgerald, Richard; Rintel, Sean (Discursive psychology: Classic and contemporary studies, 2015)
This chapter shows three areas of intersection in the emergence of Discursive Psychology(DP) and membership categorisation analysis(MCA). The chapter outlines how the initial use of Sacks' category work was directed towards psychological topics at a time when the ideas were largely confined to the sociological fields of ethnomethodology and conversation analysis. Edwards' goal, as part of DP, is the respecification of psychological concepts, especially around the use of language as a window into the brain. With this stated goal Edwards uses Sacks' work and insights to offer a skillful critique of cognitive psychology and the understanding of how categorisation is used. Edwards provides an extended review of Sacks' lectures in Sacks and psychology, introducing more aspects of Sacks relate to some conceptual, analytic, and programmatic areas of cognitive psychology. The overall aim of Sacks and psychology is to argue how Sacks directs our attention towards understanding members' category work as social action rather than mental schemas.